PENGEMBANGAN MODEL PANDUAN PEMBELAJARAN KETERAMPILAN PROSES SAINS BIOLOGI SMA/MA - asih, triana (BIOEDUKASI (Jurnal Pendidikan Biologi), 2015)
Abstract: Science learning in senior high school was designed with the goal of achieving the competencies of graduates that includes aspects of attitudes, skills, and knowledge competency. Skill aspect refers to the Scientific Approach. Skills such as observing the process are observing, trying, processing, serving, and reasoning. All of these skills, leading to the aspects that exist within SPS. Learning needs analysis conducted by researchers at the SMA/ MA class XI IPA that is in the Purbolinggo district of East Lampung SPS shows a lack of provision in the learning process. Supposedly, learning basedÂ  on SPS is further enhanced, the researchers created a learning guide model based on SPS. The objectives of the reasearch: 1) produce a learning guide model based on SPS class XI, 2) improve outcomes (process) and output (learning cutcomes) biology learning class XI. Type of the research is Research and Development (R&D). The research was conducted in SMA N 1 Purbolinggo in class XI Science. Procedures R&D is adapted from Borg and Gall consisting of five steps: 1) literature review and the results of relevant research, 2) Design and carry out preliminary study, 3) the development/conceptualization models, 4) test the model through experimentation, 5) revision of the model. conclusion; 1) learning guide SPS models has been validated by the user and learning experts, instrument validation, model validation, and it is suitable.Â